Drama-Based Speaking Module In Improving Mrsm Students’ English Speaking Performance - Jamali, Adz Jamros (2021)
This study aims to develop a teaching module named Drama-Based Speaking Module (DSM) as an assistant or tool to guide upper secondary school teachers to conduct the teaching of speaking in class. This module focuses in helping and assisting the English teachers in conducting speaking lessons based on National Curriculum (KPM, 1996), Integrated Curriculum for Secondary Schools (ICCS) - Curriculum Specifications: Bahasa Inggeris (KPM, 2003) and the ASSURE Instructional Model (1995). The development of DSM is aimed in targeting to the problems faced by the secondary school students (namely MARA Junior Science College (MRSM)) in their performance in speaking English and in the lack of existing module that focuses on the teaching and learning of speaking skills in classroom lessons. Two theories named Gardner’s Theory of Multiple Intelligences (MI) and Krashen’s Affective Filter (AF) are the ground in the development of the module. This module is a student-centered component and contains systematic outlined activities based on the learning objectives and outcomes in keeping its features of being user-friendly, informative, and practical. A mixed method approach is used, involving an MRSM (Maktab Rendah Sains MARA) as the sample. Quantitative scoring data – Speaking Test, Qualitative interviews and document analysis are the main methods used to collect the data. Findings have proven that the use of DSM helps teachers to cater students’ necessities in the process of teaching and learning of speaking. It has positive impacts on teachers’ pedagogical knowledge and provides an active learning process. DSM enhances communication skills in interacting actively in groups, cooperating and helping each other and completing the tasks. This study suggests that DSM is highly recommended and beneficial for both teachers and students; as DSM can be incorporate into their lessons and it focuses on students’ interest. It is hoped that DSM will serve as a useful resource material for MRSMs in specific and English subject as a whole